Prefiks /t-/ pada Konjugasi Verba Imperfektif Bahasa Arab, dalam Tinjauan Optimality Theory / Prefix /T-/ In the Conjugation of the Arabic Imperfective Verb, In Optimality Theory Perspective - Mardiah, Zaqiatul; Hizbullah, Nur (Diwan: Jurnal Bahasa dan Sastra Arab, 2021)
هناك نوعان من ضمائر سوابق أكثر إثارة للمناقشة في تصريف الأفعال المضارعة في اللغة العربية، وهما/ي/ و/ ت/. ويتركز النقاش حول علاقة الشكل والمعنى لتلك الضمائر التي تم تداخل بعضها مع بعض لتحديد معناها المراد. وضمير الغائبات يستخدم بـ/ي/ مع أنّها مستخدمة أيضا في التعبير عن ضمير الغائب. والظاهرة الأخرى أنّ /ت/ تدل على الغائبة والغائبتين بحيث إنّها تُستَخدم كذلك للتعبير عن المخاطب والمخاطبة. والسؤال في هذه الدراسة هو كيف تعيين كل من هذه السوابق بمعنى واحد من أجل الخوارزمية. فمن خلال استخدام نظرية المفاضلة أو المعروفة ب- optimality theory ، يمكن الحلّ على هذا التداخل بتحقيق علاقة فردية بين الشكل والمعنى من أجل صياغة الخوارزمية. يعد قيد تقسيم الميزة * من Xu أحد الأدوات التي يجب توجيهها في إنشاء الشكل الأفضل. وأوضحت نتائج الدراسة أن وظيفة /ت-/ لتعبير المخاطب والمخاطبة برمز / ت-/ 2 و أن وظيفة / ي-/ للتعبير الغائب و الغائبة . الكلمات المفتاحية : ضمائر سوابق ؛ تصريف الأفعال المضارعة؛ تقسيم الميزة. Abstract: Two prefix pronouns that often debated in the imperative verb conjugation in Arabic namely /y-/ and /t-/. The overlapping relationship of form and meaning in the two prefixes is the problem. The plural feminine third person pronoun is expressed by the prefix /y-/, whereas /y-/ also expresses the masculine third person pronoun. The singular and dual feminine third person pronouns are realized by the prefix /t-/, whereas /t-/ also denotes the second person. The way of mapping each prefix related to the meaning based on the algorithm. These problem can be overcome through the paradigm of Optimality Theory which revealed the relationship between form and meaning due to the algorithm formulation. Xu’s constraint is one of the instruments to guide us generate the most optimal form. This research revealed that the personal pronoun of the second person symbolized by /t-/ while the third person was symbolized by /y-/.